THE ISSUE OF INTERACTIVE ORGANIZATION OF THE ENGLISH LANGUAGE MODULE IN VOCATIONAL SCHOOLS - Mahmudova Shahnoza (TADQIQOTLAR.UZ, 2024)
Annotation: The article discusses the requirements for the curriculum and the use of different methods in the lessons. Also, the reforms in the professional education system in Uzbekistan, its important issues and the concept of professional education are discussed. Also, the main requirements for the development of the Calendar subject plan were discussed.